al-Fikr al-Yahudi : bayna ta'jij al-sira'at wa-tadmir al-hadarat - 'Uways,'Abd al-Halim. (al-Haram, al-Jizah : Markaz al-I'lam al-'Arabi, 2003)
Judaism; religion and state; Israel.
Keywords: Protocols of the wise men of Zion; Zionism; Zionism and Judaism; Jewish-Arab relations